2000
DOI: 10.4049/jimmunol.165.8.4329
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 and IL-15 Receptor Selectively Regulate Differentiation of Common Mucosal Immune System-Independent B-1 Cells for IgA Responses

Abstract: We show in this report a new regulatory role for IL-15 and IL-15R in the development of B-1 cells and their differentiation into IgA-producing cells. Mucosal IgA levels were found to be inhibited by anti-IL-15 mAb treatment in vivo, but enhanced by administration of rIL-15, while serum IgA levels remained unaffected. Mucosal B-1 cells preferentially proliferated in response to IL-15 in vitro. When mucosal B-1 and B-2 cells were separated into surface (s)IgM+sIgA− and sIgM−sIgA+ fractions, IL-15R-specific mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 51 publications
4
49
1
Order By: Relevance
“…IL-2 has been shown to be essential to IgA expression in multiple species including cattle (38). IL-2 has been proposed to be an important factor in the terminal differentiation of sIgA ϩ B-2 cells whereas IL-15 has been shown to lead to the enhancement of IgA expression from B-1 but not B-2 cells in mice (39). Mucosal B-1 cell development into IgA-secreting cells has been linked to type 2 cytokines like IL-5.…”
Section: Discussionmentioning
confidence: 99%
“…IL-2 has been shown to be essential to IgA expression in multiple species including cattle (38). IL-2 has been proposed to be an important factor in the terminal differentiation of sIgA ϩ B-2 cells whereas IL-15 has been shown to lead to the enhancement of IgA expression from B-1 but not B-2 cells in mice (39). Mucosal B-1 cell development into IgA-secreting cells has been linked to type 2 cytokines like IL-5.…”
Section: Discussionmentioning
confidence: 99%
“…These antigen-sensitized cells leave the PP and contribute to the subsequent induction of Salmonella-specific IgA response in the distant intestinal LP by means of CMIS. In addition to the wellcharacterized CMIS-dependent IgA induction pathway, recent evidence suggests the presence of an additional IgA induction pathway that is independently operated from the PP-originated CMIS (13)(14)(15). Interestingly, it also has been reported that induction of intestinal mucosal IgA against the commensal bacteria was independent from T cell help and organized lymphoid tissue (16).…”
mentioning
confidence: 99%
“…A report suggested that IL-15 promoted IgA synthesis at definite mucosal sites, but its impact on 'natural' IgM production by B-1 cells remains unresolved. 21 The immunization of animals with LPS of Francisella tularensis live vaccine strain (Ft LVS) showed protection against attenuated Ft LVS in which opsonizing IgM specifically derived from B-1a cells had played an important role. 41 Our data show that IL-15, which is expressed by enterocytes and found at the mucosal surfaces of the intestinal epithelium, directly augments IgM and IgA production.…”
Section: Il-15 Augmented Igm and Iga Expressionmentioning
confidence: 99%
“…19 Although IL-15 has several important and well-documented roles in regulating T-cell function, including restraining tumorigenesis, the interplay between IL-15 and B-1a cells has received little attention. A few studies have demonstrated that IL-15 stimulates B cell proliferation and immunoglobulin synthesis, 20,21 indicating that the role of the cytokine in regulating B-1a cells could be important because these cells are the key players of mucosal immunity.…”
Section: Introductionmentioning
confidence: 99%